Warm inflation - Ramos, Rudnei (Cadernos de Astronomia, 2023)
The original ideia of inflation, also known as coldinflation, arised to solve a number of problems associated with theBig Bang model. Warm inflation is a reformulation of theinflationary dynamics such as to make a more precise bridge withpossible microscopic models that can be able to lead to suchdynamics and which is believed to have happened in the primordialUniverse. The connections with the physics of quantum field theory,statistical mechanics and thermodynamics become more transparent inwarm inflation, which makes it a more appropriate formulation whenwe want to compare its results and predictions with theobservational data. In this article, I review the motivations behindthe idea of warm inflation, its origin from first principles and howit can provide a description which is more consistent, both from atheoretical and observational point of views, than cold inflationcan give.
Keywords: cosmology; primordial universe; warm inflation